IMPACT OF FEED RATE ON ROUGHNESS OF THE CUT SURFACE, DURING CUTTING DRY BEECH WOOD WITH A CIRCULAR SAW - Temelkova, Anastasija (FDTME-Skopje, 2023)
The feed rate during mechanical processing of wood is one of the factors that has a high influence on the roughness of the cut surface. The roughness of the cut surface caused by traces of the cutting tool (the main and secondary blades of the teeth) has an influence on the hydrothermal treatment and all other mechanical treatments of the wood. Greater roughness, due to faster evaporation of moisture from the wood, increases the percentage of drying errors. On the other hand, higher roughness reduces the utilization rate of the wood. For this purpose, in this paper, the dependence of the feed rate on the roughness of beech wood during cutting of dry wood with a circular saw is investigated, with the intention of determining the optimal cutting conditions for obtaining lower values of the roughness. In this research, three diferent feed rate were applied (U1=12 mmin-1 , U2=16 mmin-1 and U3=20 mmin-1) for a constant cutting height of 45 mm in dry beech wood with humidity W=10±1%. The measurements were made with a circular saw with diameter of D=250 mm, number of teeths Z=40 and width of the cut b=3,2 mm. The number of revolutions is n=5500 min-1 . Roughness measurements were taken with a digital comparator, according to the Rmax criterion. The obtained results show a pronounced significance, i.e. directly proportional dependence of the roughness of the cut surface on the feed rate
Keywords: beech wood, circular saw, roughness, the feed rate